Influence De L’exploitation Artisanale Du Sable Sur La Santé Et La Sécurité Des Artisans Et L’environnement: Cas De La Carrière De Nkol’Ossananga, Région Du Centre Cameroun - Clautaire Mwebi Ekengoue; Rodrigue Fotie Lele; Armand Kagou Dongmo (European Scientific Journal, ESJ, 2018)
Sand is classified among the low value development minerals, even though it is massively used in the world. The exploitation of that construction mineral at Nkol’Ossananga, around Yaounde, is done by craftsmen in unsafe conditions, such as: the exposure to a wide range of diseases and the destruction of the environment. We carried out a study on occupational health and safety and environmental impacts on the Nkol’ossananga site. Our method consisted firstly of the bibliographic review, sandpit quarry investigations afterwards, and lastly the data analysis. Tabulation of results showed that the population in the site is essentially threatened by diseases such as dysentery (15%), fibromyalgia (25%), typhoid fever (55%), otalgia (10%), ocular pains (15%), and malaria (45%). Craftmen work without any personal protective equipment (PPE) and are often victims of drowning and bacterial infections. The high demand of sand in Yaoundé involves the development of the activity in other sites and, in consequence, there is a deforestation and disappearance of many animals and vegetables species. The soil and water pollution is also noticeable due to pouring of engines waste oil in the site.